PENGARUH PERADABAN ISLAM TERHADAP KEBUDAYAAN MASYARAKAT ARAB MELAYU DI JAMBI KOTA SEBERANG - Putriana, Tike (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
This paper discusses the influence of Islamic cultural civilization on the Arab-Malay community in Jambi, Sebrang City. This study aims to identify the influence of Islamic culture on society in Arab Malay. The method used in this paper contains four stages, namely heuristics, source criticism, interpretation and historiography. The types of sources used in writing this research are sources from literature studies with historical analysis techniques using interpreters in historical facts which include books, documents and journals related to the influence of Islam in Jambi. The results of this study indicate that Islamic civilization entered Jambi from traders via the Batanghari river route and the arrival of ships from the Turkish sultanate led by Ahmad Barus who was stranded in Polo Behalo and destroyed idols so that Ahmad Barus was nicknamed Datuk Paduko Berhalo. The development of Islam in Jambi has had influences in various fields, especially on the Malay Arab community in Jambi, Sebrang City. Some of the influences that can be seen from Islamic civilization on the culture of the Jambi Malay Arab community, Sebrang City, namely the zapin dance, the dan syarah dance, gambus music, burdah, Assyura day, batik, eating together, hadrah or kompangan, visiting the graves of cooking, nisfu sya'ban, nginau, nuak and shaving babies' hair.